Two Seira Lubbock 1869 (Collembola, Arthropleona, Entomobryidae) new to science, with remarkable secondary sexual characters - Zeppelini, Douglas; Bellini, Bruno Cavalcante (Zootaxa, 2006)
Two new species of Seira Lubbock 1869 are described and illustrated. The males of these species show modifications in the fore legs, probably associated with sexual courtship and/or mating behavior. Despite the similarity of the modifications of the two species, they are not otherwise similar. Thus the similarity is due to convergence rather than homology. These are the first records of sexual dimorphism other than genital openings in Entomobryidae.